2002
DOI: 10.1007/s00422-002-0332-3
|View full text |Cite
|
Sign up to set email alerts
|

Scene segmentation by spike synchronization in reciprocally connected visual areas. II. Global assemblies and synchronization on larger space and time scales

Abstract: We present further simulation results of the model of two reciprocally connected visual areas proposed in the first paper [Knoblauch and Palm (2002) Biol Cybern 87:151-167]. One area corresponds to the orientation-selective subsystem of the primary visual cortex, the other is modeled as an associative memory representing stimulus objects according to Hebbian learning. We examine the scene-segmentation capability of our model on larger time and space scales, and relate it to experimental findings. Scene segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 68 publications
(115 reference statements)
2
34
0
1
Order By: Relevance
“…The more stimuli that are presented, the less time an assembly representing a single stimulus can be in the fast state because of the interplay of competition and habituation. These findings may be related to experimental results investigating attention and shrinking receptive fields (Moran and Desimone 1985;Reynolds and Desimone 1999; see also Knoblauch and Palm 2002). c Summed spike records of ten different activated patches representing the triangle (rows 6-9), ellipse (rows 3-5), and rectangle (rows 0-2) stimuli in population P .…”
Section: Superposition Of Several Stimulimentioning
confidence: 62%
See 2 more Smart Citations
“…The more stimuli that are presented, the less time an assembly representing a single stimulus can be in the fast state because of the interplay of competition and habituation. These findings may be related to experimental results investigating attention and shrinking receptive fields (Moran and Desimone 1985;Reynolds and Desimone 1999; see also Knoblauch and Palm 2002). c Summed spike records of ten different activated patches representing the triangle (rows 6-9), ellipse (rows 3-5), and rectangle (rows 0-2) stimuli in population P .…”
Section: Superposition Of Several Stimulimentioning
confidence: 62%
“…Since axonal delays are quite small (see Appendix B.3) and the associative memory is fully connected (i.e., synapses between any pairs of neurons are possible), we rather interpret area C as one or several cortical columns of a higher visual area (Braitenberg and Schu¨z 1991), e.g., V4 or IT. In the second paper (Knoblauch and Palm 2002) we simulate a larger variant of this model to investigate more-global effects, where also area C is organized topographically.…”
Section: Area Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the transmission delays between hemispheres can reach many tens of milliseconds ( [12], Fig. 1B), nonlocal synchronization e ects in cortex have been discussed controversially: modeling studies have indicated that in-phase synchronization requires synaptic delays smaller than 1 3 or 1 4 of the oscillation period [6,9,10]. For 50 Hz oscillations the zero-phase condition (delay ¡ 20 3 ms) is obviously not met.…”
Section: Introductionmentioning
confidence: 99%
“…Это противоречит как экспериментальным данным, так и теоретическим представлениями ТВК, согласно которым активность нейронов, представляющих один объект, должна быть синфазной. Авторами предложено несколько вариантов модификации модели для преодоления этой трудности [37]. Один из вариантов был исследован более подробно методами имитационного моделирования.…”
Section: сегментация и памятьunclassified